France Debates International Student Fees - de Gayardon, Ariane (International Higher Education, 2016)
The question of international students’ tuition fees has sparked debates in many of the European welfare states. One of the latest countries to face such a debate was France, where the matter is complicated by the African origin of half of the mobile students. This article looks at the French context to provide insights on the questions and concerns that the establishment of such policies should raise.